1980
DOI: 10.2134/agronj1980.00021962007200050021x
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Legume Introduction, and Persistence in Permanent Pastures1

Abstract: Permanent pasture in hill land is frequently on steep and/or rough land unsuited to frequent travel with ground equipment. Ways are needed to introduce and maintain legumes on such land. This study involved 18 treatments using P (208 kg/ha), Mo (2.2 kg/ha), lime (6.5 metric ton/ha), rototilling and white clover, Trifolium repens L. seed (2.2 kg/ha) in various combinations on two permanent pastures in central West Virginia to investigate ways of increasing yields and introducing legumes, and to determine persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…During the experiment, the area was rotationally grazed and at each grazing most of the forage was removed. These results under grazing are nearly identical to those reported from earlier clipping studies in West Virginia (BAKER 1980). WOLFE (1970) presents the following as a typical pattern of development when native pastures are improved in Australia.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…During the experiment, the area was rotationally grazed and at each grazing most of the forage was removed. These results under grazing are nearly identical to those reported from earlier clipping studies in West Virginia (BAKER 1980). WOLFE (1970) presents the following as a typical pattern of development when native pastures are improved in Australia.…”
Section: Resultssupporting
confidence: 84%
“…Experiments have shown that hill pastures can be improved both in terms of quality and quantity by lime and fertilizer applications (BAKER 1980, BROWN et al 1960, VAN KEUREN 1976. SMITH et al (1944) concluded that satisfactory stands of various grasses and legumes can be obtained quickly by tillage, treatment BRYAN with lime and P, and seeding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also was hypothesized that soil fertility, especially P and K concentrations, and rotational grazing had a major influence on the success of clover establishment (Dunlop et al . ; Baker ; Hill and Hoveland ; Frame ). Soil fertility and rotational grazing were not manipulated in that study, however, so the importance of these variables could not be quantified precisely.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that legumes can increase the productivity and quality of a grass pasture. In order to secure a legume component in the sward, legumes have been successfully established in both cool-season and warm-season grass sods by reduced tillage methods (Baker 1980;Bryan 1985;Decker et al, 1969;Dovel et al, 1990;George et al, 1995;Mueller and Chamblee, 1984;Olsen et al, 1981;Taylor et al, 1969). Frost-seeding has also been documented to successfully establish legumes in cool-season grasses when Graber (1927) established yellow sweetclover in Kentucky bluegrass sods, and more recently by George et al (1995) and Gettle et al(1996) in warm-season grasses.…”
Section: Legume Establishment and Persistencementioning
confidence: 99%